2008
DOI: 10.1080/02640410802287063
|View full text |Cite
|
Sign up to set email alerts
|

Postural tremor and control of the upper limb in air pistol shooters

Abstract: A postural tremor appears whenever someone attempts to maintain a steady position against gravity. We examined the postural tremor that occurred while air pistol shooters were taking aim so as to compare the coordinative control of the shooters and to identify the features critical to successful shooting. Ten elite and ten pre-elite athletes participated in pistol shooting at 10 m, and the postural tremors in the pistol and upper limb were recorded with lightweight accelerometers. Exploratory analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 29 publications
0
52
0
11
Order By: Relevance
“…Debido a que el tiro olímpico es un deporte en el que el uso de armas es imprescindible, la mayoría de estudios realizaron pruebas en las que se utilizó un arma para evaluar esta capacidad (Pellegrini & Schena, 2005;Tang et al, 2008). Sin embargo esta necesidad supone una importante limitación a la hora de realizar pruebas de selección de talentos en escuelas o polideportivos donde el uso de cualquier tipo de arma puede no estar permitido.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Debido a que el tiro olímpico es un deporte en el que el uso de armas es imprescindible, la mayoría de estudios realizaron pruebas en las que se utilizó un arma para evaluar esta capacidad (Pellegrini & Schena, 2005;Tang et al, 2008). Sin embargo esta necesidad supone una importante limitación a la hora de realizar pruebas de selección de talentos en escuelas o polideportivos donde el uso de cualquier tipo de arma puede no estar permitido.…”
Section: Discussionunclassified
“…En la misma línea, (Tang, Zhang, Huang, Young, & Hwang, 2008) observaron que la estabilización del complejo arma-brazo está íntimamente relacionado con el rendimiento deportivo, evidenciando los sujetos de mayor nivel deportivo una mayor capacidad para estabilizar el arma.…”
Section: Introductionunclassified
“…Goodman and Kelso (1983) showed that this phase window corresponds to the peak of momentum of the oscillations in the direction of the discrete movement. Interestingly, it has been shown that professional pistol shooters press the trigger in phase with their involuntary tremor, while beginners try to immobilize themselves before shooting (Tang et al (2008)). …”
Section: The Combination Of Discrete and Rhythmic Movementsmentioning
confidence: 99%
“… Factores técnicos: la estabilidad del arma (Hawkins y Sefton, 2011;Tang, Zhang, Huang, Young y Hwang, 2008), el momento de disparo (Konttinen, Landers y Lyytinen, 2000;Viitasalo et al, 1999;Zatsiorsky y Aktov, 1990), la limpieza en el disparo (Mononen, Viitasalo, Era y Konttinen, 2003) o el tiempo de ejecución de disparo (Walmsley y Williams, 1994).…”
Section: Marco Teóricounclassified
“…Parece ser que los tiradores de élite tienen menores movimientos de la pistola en los tres ejes, teniendo más movimiento vertical que lateral algo que no sucede en los tiradores de menor nivel (Pellegrini y Schena, 2005;Tang et al, 2008) .…”
Section: Relación Entre La Dirección De Los Movimientos De La Parada unclassified